1976
DOI: 10.1159/000127888
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Mucosal Lesions in Shock

Abstract: Mucosal lesions were produced in feline small intestine by evoking a simulated intestinal shock (local hypotension at 30 mm Hg and stimulation of regional sympathetic vasoconstrictor nerves at 6 Hz for 2 h). The degree of mucosal damage was correlated to the level of intestinal blood flow. Microscopically characteristic lesions developed regularly in the small intestinal mucosa when intestinal blood flow was reduced below 12 ml/min × 100 g during the regional shock. The mucosal damage was graded histologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Nevertheless, the mucosal lesions observed in the cat seem to be caused by hypoxia since they are prevented by intraluminal perfusion with oxygenated saline during the shock period but not by perfusion with nitrogenated saline (Haglund,Abe,Ahr6n,Braide,and Lundgren,to be published). The apparent paradox with hypoxic villous lesions in the face of almost unchanged villous blood flow can be explained by short-circuiting of oxygen in the intestinal countercurrent exchanger at the villous base and in the deeper layers of the mucosa (Lundgren, 1967;Ahren and Haglund, 1973;Haglund, 1973;Haglund et al, 1973). In the cat, such a 'shunting' has been demonstrated during 'resting' conditions (Kampp et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the mucosal lesions observed in the cat seem to be caused by hypoxia since they are prevented by intraluminal perfusion with oxygenated saline during the shock period but not by perfusion with nitrogenated saline (Haglund,Abe,Ahr6n,Braide,and Lundgren,to be published). The apparent paradox with hypoxic villous lesions in the face of almost unchanged villous blood flow can be explained by short-circuiting of oxygen in the intestinal countercurrent exchanger at the villous base and in the deeper layers of the mucosa (Lundgren, 1967;Ahren and Haglund, 1973;Haglund, 1973;Haglund et al, 1973). In the cat, such a 'shunting' has been demonstrated during 'resting' conditions (Kampp et al, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…During hypotension plasma mean transit time in the villi is greatly reduced from about 5 s to about 25 s , and the effectiveness of the countercurrent exchanger is correspondingly increased. In this situation, the villous tip is very likely to be anoxic even in the face of unchanged blood supply (Haglund, 1973;Haglund et al, 1973). Blood flow studies on humans have revealed a close qualitative and quantitative similarity betweencatandman (Hulten et al, 1972;Hulten et al, 1976) and have also provided experimental support for the existence of an intestinal countercurrent exchanger in the human gut.…”
Section: Discussionmentioning
confidence: 99%
“…Together these two layers provide a dynamic and regulated barrier allowing selective passage of luminal contents into the intestinal wall. Loss of the epithelial/mucus layer integrity is a common feature in gastrointestinal diseases [1], [2] and intestinal ischemia encountered in different forms of shock [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mucin glycoprotein is the major constituent of the mucus barrier (18) whereas enterocytes with their adherens and tight junctions make up the epithelial barrier (19). During ischemia the integrity of the mucosal and epithelial barriers become compromised (20, 21); our hypothesis is that disruption of these barriers during intestinal ischemia allows pancreatic digestive enzymes to enter the intestinal wall and thereby exacerbate intestinal injury.…”
Section: Introductionmentioning
confidence: 99%